Toll-like receptor 2/6-stimulated HMC-1 mast cells promote keratinocyte migration in wound healing - Jiyun Kwon; Kyung-Ah Cho; So-Youn Woo (PLoS ONE, 2025)
Mast cells, immune sentinels that respond to various stimuli in barrier organs, provide defense by expressing pattern recognition receptors, such as Toll-like receptors (TLRs). They may affect inflammatory responses and wound healing. Here, we investigated the effect of TLR2/6-stimulated mast cells on wound healing in keratinocytes. The human mast cell line HMC-1 was treated with the TLR2/6 agonist FSL-1, and the conditioned medium (CM) was collected from untreated cells (HMC-1 CM) and FSL-1-stimulated cells (FSL-1-HMC-1 CM). Cell migration was evaluated in keratinocyte cells (HaCaT) treated with HMC-1 CM and FSL-1-HMC-1 CM via scratch and Transwell assays. Mice were treated with HMC-1 CM, FSL-1-HMC-1 CM, and FSL-1. Wound closure was measured, and tissue regeneration was assessed using hematoxylin and eosin staining. Growth factor expression levels were evaluated to identify the factors affecting wound healing. The tryptase inhibitor APC 366 was treated with HMC-1 CM and FSL-1-HMC-1 CM in a scratch assay. This study revealed that HMC-1 CM affected HaCaT cell migration, which was facilitated by FSL-1-HMC-1 CM. HMC-1 CM promoted tryptase-dependent HaCaT migration. Moreover, FSL-1-HMC-1 CM enhanced wound healing in C57BL/6J mice in vivo. Our findings indicated that TLR2/6-stimulated mast cells contributed to skin homeostasis by promoting tryptase-dependent wound healing.